Screening, identification and enzyme production conditions optimization of a cellulase-producing yeast - RAN Guangyao, TANG Jiadai, ZHAO Yimei, MENG Zhuoni, LONG Yafei, GUO Min, GUO Ju (Zhongguo niangzao)
In order to screen high cellulose-producing yeast, cellulose-producing yeasts were screened from the fermented grains of sauce-flavor (Jiangxiangxing) Baijiu by Rose Bengal Agar and Congo Red Medium, and the screened strains were identified by morphological observation, physiological and biochemical tests, and molecular biology technique. The tolerance was investigated and the enzyme production conditions were optimized. The results showed that a cellulase-producing strain JXJP-Y19 was screened, and the strain JXJP-Y19 was identified as Yarrowia lipolytica. The temperature, ethanol, and pH tolerance of the strain JXJP-Y19 were 39 ℃, 8%(V/V), and 3, respectively, showing good tolerance to environmental stress. The optimal enzyme production conditions were as follows: bran as carbon source, cottonseed cake as nitrogen source, inoculum 1%, initial pH 6 and fermentation temperature 30 ℃. Under these optimal conditions, the activities of filter paper enzyme, exoglucanase and β-glucosidase produced by the strain JXJP-Y19 were (0.913±0.025) U/ml, (1.272±0.025) U/ml and (0.937±0.030) U/ml, respectively, which were 2.15 times, 1.81 times, and 1.94 times higher than before optimization. The strain JXJP-Y19 showed good cellulase activity and could be used as a potential strain for cellulose bio-degradation utilization.